Investigation of microstructure and corrosion behavior of friction stir welded dissimilar joints AA5754-O to AA5052-O - Atef Hassanein; Ibrahim Hassab-Allah; Hamada Hussein Morsy; Mohamed AbuOkail (JES: Journal of Engineering Sciences)
The durability of maritime structures is critically affected by harsh marine environments, where saltwater exposure accelerates corrosion and compromises structural integrity. This study investigates the influence of key friction stir welding (FSW) parameters on the microstructure and corrosion behavior of dissimilar aluminum alloys AA5754-O and AA5052-O, which are commonly used in marine applications. A systematic experimental design based on Taguchi’s L16 orthogonal array was employed, incorporating four process variables: rotational speed (710–2000 rpm), traverse speed (20–80 mm/min), tool tilt angle (1°–4°), and pin profile (triangular, taper threaded, cylindrical threaded). Electrochemical corrosion tests (potentiodynamic polarization), microstructural analyses (optical and SEM), and statistical tools (ANOVA) were used to evaluate weld integrity and identify optimal parameters. Results demonstrate that defect-free joints with enhanced corrosion resistance are achieved using a triangular pin profile at 1400 rpm, 40 mm/min, and 1° tilt angle. In contrast, welds produced with a tapered and cylindrical threaded tools under lower travel speed and higher tilt angle exhibited reduced corrosion resistance. This study provides practical insights into optimizing FSW conditions to fabricate durable, corrosion-resistant joints for marine environments, addressing a key gap in current dissimilar alloy welding research.